Novel Agents for the Treatment of Pancreatic Adenocarcinoma - Cheng, Haiying; Merika, Eirini; Syrigos, Kostas; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
There are urgent needs to develop novel and more effective regimens to improve outcomes of pancreatic cancer given its dismal prognosis and limited treatment options. Several phase I clinical trials involving novel agents were recently presented at the 2011 American Society of Clinical Oncology (ASCO) Annual Meeting. It appears that hedgehog inhibition with IPI-926 was well-tolerated and might be effective in treating pancreatic cancer when combined with gemcitabine. The survival benefits will be tested in the following randomized phase II trial. The new combination of gemcitabine and blockade of checkpoint kinases with AZD7762 showed an acceptable safety profile. Furthermore, inhibition of PI3K by BAY80-6946 was well tolerated with PET-CT suggesting reduction in FDG uptake in some pancreatic cancer. The benefits of above novel agents/regimens need to be further tested in phase II trials. Image: Hedgehog pathway (cancer cell)